Infections caused by rare mold fungi in hematology - I. I. Kalinina; U. N. Petrova; O. V. Goronkova; D. D. Baidildina; V. V. Sinitsyna; L. A. Khachatryan; M. A. Maschan; G. A. Klyasova; A. A. Maschan (Онкогематология, 2014)
Worldwide distribution of mold fungi and their extremely danger for immune compromise patients makes this issue one of the unsolved problems in modern oncology. Three cases of rare fungal infections in children with hematological malignancies are described. In the first case infection caused by Acremonium spp. in AML patients was controlled after voriconazole therapy and granulocytes recovery. The second patients with aplastic anemia died as a result of invasive fungal infection caused by Fusarium spp. despite of combined antifungal therapy and granulocytes transfusions. In the third case diagnosis of Mucor mycosis was made only at autopsy